Recycling of Solid Waste for Biofuels and Bio-chemicals - Karthikeyan, Obulisamy Parthiba; Heimann, Kirsten; Muthu, Subramanian Senthilkannan (Environmental Footprints and Eco-design of Products and Processes, 2016)
This book presents the latest advances in and current research perspectives on the field of urban/industrial solid waste recycling for bio-energy and bio-fuel recovery. It chiefly focuses on five main thematic areas, namely bioreactor landfills coupled with energy and nutrient recovery; microbial insights into anaerobic digestion; greenhouse emission assessment; pyrolysis techniques for special waste treatment; and industrial waste stabilization options. In addition, it compiles the results of case studies and solid waste management perspectives from different countries. .